2017
DOI: 10.1186/s12957-016-1065-4
|View full text |Cite
|
Sign up to set email alerts
|

Pasteurized autograft reconstruction after resection of periacetabular malignant bone tumours

Abstract: BackgroundThe treatment of periacetabular malignant bone tumours is challenging. Many methods of reconstruction after internal hemipelvectomy have been reported and each method has its own limitations. The aim of this study was to evaluate the oncological and functional outcomes of pasteurized autograft reconstruction after resection of periacetabular malignant bone tumours.MethodsTen patients (six male, four female) with periacetabular malignant tumours, who underwent resection and reconstruction with pasteur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
(84 reference statements)
1
13
0
Order By: Relevance
“…The cumulative incidence of implant failure in this study was satisfactory compared with the other reconstructions 54‐58 . Bus et al 11 reported that the cumulative incidence of implant failure of LUMiC, the other stemmed‐cone acetabular prosthesis, was 17.3% for mechanical reasons and 9.2% for infection at 5 years.…”
Section: Discussionsupporting
confidence: 50%
“…The cumulative incidence of implant failure in this study was satisfactory compared with the other reconstructions 54‐58 . Bus et al 11 reported that the cumulative incidence of implant failure of LUMiC, the other stemmed‐cone acetabular prosthesis, was 17.3% for mechanical reasons and 9.2% for infection at 5 years.…”
Section: Discussionsupporting
confidence: 50%
“…Autograft reconstructions were used in five studies, involving 54 patients. 8 , 14 , 27 , 33 , 60 In this technique, the resected hemipelvis is pasteurised with heat to sterilise the malignancy and re-implanted with plates, screws, and prostheses. Most, 47 (87%), were for a primary malignancy.…”
Section: Resultsmentioning
confidence: 99%
“…The high risk of complications has been a major problem associated with surgery for pelvic sarcomas. The reported rate of major complications, which required additional surgical interventions, has been 28% to 65% in endoprosthetic reconstruction, 29% to 60% in allograft reconstruction, 20% to 57% in recycled autograft reconstruction . Among these major complications, deep infection is the most serious and frequent one, and is a common cause of implant failure .…”
Section: Discussionmentioning
confidence: 99%
“…been 28% to 65% in endoprosthetic reconstruction, 23,29,[33][34][35][36]49,61,62 29% to 60% in allograft reconstruction, 39,48,63,64 20% to 57% in recycled autograft reconstruction. 41,43,65 Among these major complications, deep infection is the most serious and frequent one, and is a common cause of implant failure. 23,66 While the details of surgical outcomes for pelvic ES involving the acetabulum has been limited, the existing publications have revealed high rates of major complications, ranging from 30% to 40%.…”
Section: Functional Outcomesmentioning
confidence: 99%
See 1 more Smart Citation